PENINGKATAN PROFESIONALISME GURU MELALUI PELATIHAN TEKNOLOGI METAVERSE UNTUK MEWUJUDKAN ASTA CITA 4 - Ahmad Shofiyuddin; Mohammad Anshori; Ahmad Tauchid (INTEGRITAS : Jurnal Pengabdian, 2025)
Digital transformation in education requires teachers to continuously enhance their professionalism, particularly in utilizing advanced technologies such as the metaverse. However, not all teachers possess the capacity and readiness to develop learning materials based on such technologies. This community service program aims to improve the professionalism of teachers at SMK Islamic Qon through training in developing metaverse-based teaching materials, in support of achieving Asta Cita 4, namely the development of human resources and gender equality. The method used is the ABCD (Asset-Based Community Development) approach, implemented in five stages: socialization, training, mentoring, evaluation, and follow-up. The results of the program indicate a significant increase in teachers' knowledge, attitudes, and skills related to the development of metaverse-based teaching materials, with success indicators reflected in the achievement of targeted competencies during training evaluations. Furthermore, teachers demonstrated increased creativity and motivation in designing more immersive and engaging learning experiences for students. In conclusion, this training program has made a tangible contribution to strengthening teacher capacity and encouraging the integration of technology into vocational education at the secondary level.